ECOPHYSIOLOGY OF FUNGUS-RESISTANT GRAPES GROWN AT THREE ALTITUDES IN THE SOUTH OF BRAZIL - Rizzolo, Rafaela Gadret; Gardin, João Peterson Pereira; de Souza, André Luiz Kulkamp; Dal Vesco, Lírio Luiz; Vieira, Hamilton Justino; da Silva, Aparecido Lima; Pescador, Rosete (ARACÊ, 2025)
Worldwide, climatic conditions change due to latitude, longitude, and altitude. Latitude directly influences the duration of the photoperiod and the intensity of solar radiation received, longitude mainly represents continentality/oceanity and altitude influences changes in climate due to atmospheric pressure. Some winegrowers seek to obtain more favorable conditions for viticulture in higher altitude areas, compensating, to a certain extent, the effect of latitude. Numerous scientific studies confirm the existence of morphological and physiological changes that occurred in the vine plant exposed to certain environmental conditions, typical of most altitude vineyards. Therefore, the objective of this work was to carry out climatic assessments at different altitudes and their interactions with the development of varieties resistant to fungal diseases. The aim of this work was to carry out climatic assessments at different altitudes and their interactions with the development of varieties resistant to fungal diseases. The varieties Aromera, Calardis Blanc, and Felicia were studied, white vines resistant to fungal diseases, cultivated in Água Doce (1329 meters), Curitibanos (1000 meters), and Videira (774 meters), cities in the state of Santa Catarina, during 2018/19 and 2019/20. The analyzes included climatic data, net photosynthesis (A), stomatal conductance (gs), transpiration (E), internal carbon (Ci), maximum quantum yield of photosystem II (Fv/Fm), non-photochemical quenching (NPQ), yield effective quantum of photosystem II (ΔF/Fm’), apparent electron transport rate (ETR), leaf area (AF), number and weight of bunches, Ravaz Index, soluble solids (SS) and total acidity (TA). Compared to cultivation at an altitude of 774 meters, the altitude of 1329 meters provided a total average decrease of 4.28ºC in temperatures, 99% in NPQ, 30% in AF, 4.65% in bunch weight, and 15% in ATT; and average total increment of 144.70 W.m-2 in radiation, 13.5Km.h-1 in wind speed, 17% in A, 81% in gs, 9% in E, 8% in Ci, 8% in Fv/Fm, 14% in the ΔF/Fm’, 45% in the ETR, 19% in the number of bunches and 9% in the SS. It is concluded that there is an adaptation to growing conditions, but they are strongly regulated by altitude and variations in climate, with higher altitude providing more favorable climatic conditions for the development of the studied varieties.